An in-depth exploration into college students’ information acquisition and evaluation behaviors during the COVID-19 infodemic - Chen, Nien-Tsu Nancy; Kee, Kimmy; Villalobos, Bianca T.; Ortiz, Miriam; Lee, HyeSun (Frontiers in Communication, 2025)
IntroductionThis study examines how vaccination-inclined and vaccination-hesitant U.S. college students acquired and evaluated COVID-19 vaccination information.MethodsIn 2021, we conducted 26 focus group discussions and used thematic analysis to identify patterns in information acquisition behaviors and trust in information sources.ResultsFindings revealed mismatches between frequently used and most trusted sources. Public health agencies were highly trusted but not commonly consulted first. In contrast, social media were frequently used for information scanning despite being the least trusted. Interpersonal sources (e.g., family) were identified as both a most and least trusted source. They were trusted for their good intention but questioned for their expertise and perceived reliance on biased sources like social media.DiscussionGiven the identified gap between information acquisition and trust, public health communication must address how college students weigh convenience, familiarity, and credibility when obtaining and evaluating health information in an environment flooded with misinformation and disinformation.